CHARACTERIZATION AND STATISTICAL CORRELATION BETWEEN CHARCOAL’S PHYSICAL AND MECHANICAL PROPERTIES OF Eucalyptus AND Corymbia CLONES - Moutinho,Victor Hugo Pereira (2017)
ABSTRACT The study aimed to analyze the physical and mechanical properties of charcoal from eucalypt clones by principal component analysis and demonstrate the relationships between these properties, in order to assess which charcoal property should aimed in the process to obtain a higher quality product. In this way, was cut eight clones of Eucalyptus and two of Corymbia, collecting three trees per clone and five disk in different heights. The disks were transformed into test samples, totaling an average of 75 samples per clones, which were carbonized under specific conditions for analysis of apparent density, compressive strength parallel to grain and linear and volumetric degradation due to high temperature. It is noteworthy that the data were weighted by disk and per tree, to an average closer to reality. For correlations, was used multivariate analysis of principal components. Herein, it is found that the apparent density of charcoal acts as the focal point of the other properties studied, and observed that as the higher the density, higher will be the compressive strength parallel to grain, the elastic modulus and the gravimetric yield.